ANALISIS PENGARUH KUALITAS LAPORAN KEUANGAN TERHADAP KEPUTUSAN INVESTASI - Rika Lidyah; Vitayanti Fattah; Endi Rustendi; Herawati Herawati; Abdul Rosid (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze and determine the effect of financial report quality on investment decisions. The population in this study are companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. Sampling in this study used the purposive sampling method. The number of samples in this study was 93 companies. The research method used is secondary research. The data analysis technique in this study uses simple linear analysis with a model feasibility test (F test) and a partial regression test (T test). The data processing process was carried out using the Statistical Package for Social Science (SPSS) program. The findings in this study are that the quality of financial reports has a significant effect on investment decisions. With a t-value of 3.637 and a significant value of 0.000. The quality of financial reports also makes a significant contribution to investment decisions, amounting to 12.8% of the variance.